German firms go international - Rolf Jungnickel; Georg Koopmann (Intereconomics, 1973)
This article offers a contribution to the topical discussion of multinationals. It describes the quantitative and qualitative identification criteria for these enterprises and analyses the internationalisation process of German firms.
Keywords: 330; Germany